Conceptualizing Innovations in Healthcare Framework and Its Implications - Akhani , Pratik N.; Deshpande , Anupriya; Agrawal , Uditkumar; Vyas , Nirali D.; Saiyed , Falak; Saiyad , Huma; Patel , Jitendra (Current Innovations in Disease and Health Research Vol. 9, 2023)
Innovations serve as the primary driver of human progress and the enhancement of the quality of life. Simultaneously, they pose challenges to established norms, solutions, and societal paradigms. Within the realm of healthcare, innovations empower us to address previously untreatable ailments and optimize the utilization of limited resources. However, they render existing healthcare technologies obsolete, necessitate the acquisition of new competencies by specialists, and demand substantial financial investments. Consequently, in this chapter, we have constructed a conceptual framework model for the evolution, acceptance, and dissemination of innovations in healthcare into Small-scale, Intermediate, and Large-scale innovations. We have conducted an analysis of the impediments and facilitators of innovations, with particular attention to meta-stability, financial considerations, innovative capabilities, and leadership. This model has been applied to three specific innovations: personalized medicine, digital health, and implant technologies. Our findings underscore the essential role of strategic innovation management in healthcare as a prerequisite for the swift development and integration of innovations, ultimately leading to the enhancement of the quality of life for the aging population.